High‐resolution observations of secondary circulation and tidally synchronized upwelling around a coastal headland. Issue 2 (1st February 2017) - Russell, P.; Vennell, R.
Abstract: The upwelling of nutrient‐rich bottom waters supports life at the oceans' surface. Secondary circulation can produce localized upwelling at headlands. Secondary circulation develops in the curved flow around headlands resulting in a loose helical flow pattern within the curved flow. The magnitude of secondary flow can be up to 20% of the depth average current. Moving vessel ADCP measurements were taken at Cape Saunders, Otago Peninsula, New Zealand. New radial basis function interpolation techniques for smoothing noisy data allows the weak horizontal secondary flow to be extracted from the stronger along shore flows. During peak floods of 1 ms −1 the measured strength of secondary flow is 0.2 ms −1 . A region of secondary flow approximately 1500 m long and 800 m wide is observed downstream of the Cape. On the inshore edge this region, areas of vertical velocity inferred from horizontal ADCP measurements using mass continuity show a localized upwelling of up to 0.007 ms −1 . Concurrent CTD measurements also show this tidally synchronized upwelling. Linear regression between upwelling from the CTD measurements and the inferred vertical velocity from the ADCP measurements show the data are well correlated, rp = 0.65. The upwelling is 4 m per hour so in this location with a mean depth of 25 m the entire water column is replacing itself with deep waters at least once during a tidal cycle. On a global scale, the cumulative upwelling from headlands and islands due to secondary circulation could be a significant source of nutrient delivery to coastal surface waters. Key Points: Secondary flow produces tidally synchronized upwelling around a coastal headland Vertical velocity can be inferred from secondary flow using mass continuity CTD measurements of vertical velocity are correlated with inferred vertical velocity from ADCP measurements